Houses dug into the ground in Ancient Nikonion in the Lower Dniester region - Mariusz Mielczarek (Fasciculi Archaeologiae Historicae, 2016)
Dugouts or semi-dugouts were typical form of the oldest Greek dwelling houses in the northern Pontus Euxinus region. The Lower Dniester region has yielded a very interesting evidence for studies on the history of houses dug into the ground. The Lower Dniester region was dominated in Antiquity by two Greek poleis, Nikonion and Tyras. Until the middle of the 5th c. BC houses dug into the ground were predominant dwelling architecture at Nikonion as well as in rural settlements on Nikonion chora. At Nikonion more than 20 houses dug into the ground are recovered. They are scattered in different places of the mound covering the remains of Ancient city. The house dug into the ground, registered as no. 196, located in the southern part of the mound and excavated in 1995, is analysed in details. The archaeological evidence confirms that the dugout no. 196 was used in the first half of the 5th c. BC. It also suggests that the dugout has been left in the middle of the 5th c. BC